In Silico Analysis of Vaginal Microbiota in Female Reproductive Health Using NCBI Database and BLAST - Bustami, Arleni; Kiranasari, Ariyani; Merizka, Engla (Indonesian Journal of Medical Chemistry and Bioinformatics, 2026)
Background: The vaginal microbiota plays a critical role in maintaining female reproductive health. Beneficial bacteria, particularly Lactobacillus species, contribute to vaginal homeostasis, whereas dysbiosis-associated bacteria such as Gardnerella vaginalis and Prevotella bivia have been linked to bacterial vaginosis and reproductive tract disorders. Publicly available nucleotide databases and bioinformatic tools provide accessible resources for studying microbial species associated with vaginal health. Objective: This study aimed to perform a simple in silico analysis of representative vaginal microbiota using publicly available 16S rRNA gene sequences retrieved from the NCBI database and analyzed using BLAST and phylogenetic approaches. Methods: Representative 16S rRNA gene sequences of Lactobacillus crispatus (NR_041857.1), Gardnerella vaginalis (NR_026079.1), and Prevotella bivia(NR_113598.1) were retrieved from the NCBI Nucleotide Database. Sequence identification was performed using NCBI BLASTn against the Nucleotide Collection (nr/nt) database. Phylogenetic analysis was conducted using MUSCLE sequence alignment and the Neighbor-Joining method implemented in MEGA11 with 1,000 bootstrap replicates. Biological interpretation was supported by a literature review of the selected bacterial species. Results: BLAST analysis demonstrated high sequence similarity (>98%), high query coverage, and E-values approaching zero for all retrieved sequences, confirming accurate species identification. Comparative analysis indicated that Lactobacillus crispatus is associated with maintenance of vaginal homeostasis through lactic acid production and protection against pathogen colonization. In contrast, Gardnerella vaginalis and Prevotella bivia are commonly associated with vaginal dysbiosis, bacterial vaginosis, and inflammatory reproductive conditions. Phylogenetic analysis revealed a clear separation between L. crispatus and the dysbiosis-associated bacterial species, reflecting their distinct taxonomic relationships. Conclusion:This study demonstrates the usefulness of publicly available sequence databases and basic bioinformatic tools for the identification and characterization of representative vaginal microbiota associated with female reproductive health. The findings highlight the contrasting biological roles of beneficial and dysbiosis-associated bacteria and provide a simple framework for introductory studies in reproductive microbiology and bioinformatics.